Law, order and freedom : A historical introduction to legal philosophy - Jacobs, F.C.L.M; Maris, C.W (Law and Philosophy Library, 2012)
Law, Order and Freedom gives an account of the history of Western legal and political philosophy, starting with the pre-Socratics and ending with Rawls. It examines in detail the development of the Enlightenment values of freedom and equality, the foremost principles of many present-day constitutions. The underlying ideal of individual autonomy, characteristic of modern times, has nevertheless been contested throughout its history. Against the background of this historical development, Law, Order and Freedom enquires further whether the modern Enlightenment values can serve as a foundation for law and society in the modern era where a great diversity of worldviews exists.             Law, Order and Freedom will be an invaluable resource for those with an interest in legal and political philosophy.